Dimensi Kedisiplinan dan Kinerja Pegawai Perum Bulog Maluku-Maluku Utara - Johar Isnain; Mohamad Arsad Rahawarin; Hendry Selanno (MAN 4 Kota Pekanbaru, 2026)
This study analyzes the relationship between discipline dimensions and employee performance at Perum Bulog Regional Office of Maluku and North Maluku. The research addresses a gap in previous studies that commonly treated work discipline as an aggregate variable and rarely examined its specific dimensions separately. A quantitative correlational design was applied using a total sampling approach; all 79 employees were invited to participate, and 27 complete questionnaires were analyzed. Pearson product-moment correlation was employed as a bivariate mapping technique. The findings show that goal and ability, compensation, punishment, assertiveness, and human relations have strong and significant correlations with employee performance, while leadership role model has a moderate significant correlation. In contrast, fairness and supervision show no significant correlation with performance. Because the data rely on a small effective sample and self-report questionnaires, the findings should be interpreted as associative rather than causal. The study contributes to human resource management by clarifying which discipline dimensions are most closely associated with employee performance and by offering practical guidance for strengthening organizational discipline policies.